Pre-season bilateral strength asymmetries of professional soccer players and relationship with non-contact injury of lower limb in the season - Izovska, J.; Mikic, M.; Dragijsky, M.; Zahalka, F.; Bujnovsky, D.; Hank, M. (SportMont, 2019)
The aim of this study was to determine the relationship between bilateral pre-season strength asymmetries and the injury of the lower limb in the season. Examined group consisted of 227 soccer players playing in the highest league competition in the Czech Republic (age 25.44±8.7, body height=182.1±6.6 cm, body weight=77.5±6.9 kg). We measured the isokinetic strength of the flexors and extensors of the knee by using the Cybex dynamometer Humac Norm at 60 m.s-1 angular speed and then we compared the bilateral asymmetries between the dominant and non-dominant lower limb in knee flexors and extensors. We retrospectively compare the injury to pre-seasonal bilateral strength imbalances between flexors and extensors of the knee. The results show that 65.9% of players who suffered non-contact leg injuries in the season had imbalances in knee extensors between preferred and non-preferred lover limb =10% difference before the season and the percentage of injured players with bilateral asymmetry of knee flexors was 67.9%. These results predict that abnormal muscle asymmetry between the lower extremities may be one of the causes of injury in the area of lower extremities.